Positive modulation of a neutral declarative memory by a threatening social event - Fernández, Rodrigo Sebastián (2015)
Memories can be altered by negative or arousing experiences due to the activation of the stress-responsive sympatho-adrenal-medullary axis (SYM). Here we used a neutral declarative memory that was acquired during multi-trial training to determine the effect of a threatening event on memory withouth emotional valence. To thgis end, participants received a new threatening social protocolbefore learning pairs of meanningless syllabes and were tested either 15´, 2 days or 8 days after acquisition. We first demostrate that this threatening social situation activates not only the SYM axis.